DETERMINANT OF COMPANY VALUE IN THE SRI-KEHATI INDEX ON THE INDONESIAN STOCK EXCHANGE - Nurlisa Borliani Siregar; Isfenti Sadalia; Amlys Syahputra Silalahi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The Sri-Kehati index is one of the indices that is an indicator of stock price movements on the Indonesia Stock Exchange. This index uses the principles of sustainability, finance, and good governance, as well as concern for the environment as benchmarks. There are many factors thought to influence the level of firm value, including corporate social responsibility, intellectual capital, and environmental performance. This study aims to determine the significance of the influence of corporate social responsibility and intellectual capital on firm value with environmental performance as a mediating variable on the Sri-Kehati Index on the Indonesia Stock Exchange. This research was conducted on all companies listed on the Sri-kehati Index listed on the Indonesia Stock Exchange, totaling 25 companies with a research period from 2017 to 2021. The research method used is PLS (Partial Least Squares), namely SEM (Structural Equation Method) based on variance. The results of this study state that corporate social responsibility has a negative and insignificant effect on firm value. Intellectual capital has a positive but not significant effect on firm value. Corporate social responsibility has a positive but not significant effect on environmental performance. Intellectual capital has a negative and significant effect on environmental performance. Environmental performance has a negative and significant effect on firm value. As well as environmental performance is not able to mediate corporate social responsibility and intellectual capital on the company's firm value on the Sri-Kehati Index.